Pendampingan Pengurusan Izin Edar SPP-PIRT dan Sertifikasi Halal Pelaku Usaha Mikro dan Kecil di Desa Situ Udik - Rina Rismaya; Dewi Juliah Ratnaningsih; Iffana Dani Maulida; Eko Yuliastuti Endah Sulistyawati; Elizabeth Novi Kusumaningrum (Altifani Journal: International Journal of Community Engagement, 2026)
Lack of knowledge and information; limited resources; the stigma of complicated procedures and lengthy application processes; and expensive financing are factors causing most micro and small enterprise (MSE) products in Situ Udik Village to not have distribution permits for Home Industry Food Production Certificates (SPP-IRT) and halal certification. This condition causes these MSE products to struggle to compete in the market and is limited in reaching a wider market. This community service program aims to determine the effect of providing training and assistance in processing SPP-IRT distribution permits and halal certification on increasing the knowledge and legality of MSE partner businesses in Situ Udik. This community service activity is carried out through several stages, including socialisation, training and assistance, and monitoring and evaluation stages. This community service activity was attended by 15 MSE partners in Situ Udik Village, Cibungbulang District, Bogor Regency. The results of this community service show that the provision of training and mentoring has been proved to significantly increase the knowledge of MSE partners as evidenced by an increase in the average pretest score (74.5%) compared to the posttest score (82.5%), and there are as many as 13 Situ Udik MSE partners who successfully obtained SPP-IRT distribution permit certificates and halal certificates. With this community service, it is hoped that it can help Situ Udik MSE actors in improving product quality and safety, so that they have competitiveness in the market and a wider market reach